THE FIRMANS OF NADIR SHAH AFSHAR TO THE KAYTAG UTSMIY AKHMAD-KHAN (PARIS COLLECTION) - Alibekova, Patimat Magomedovna (History, Archeology and Ethnography of the Caucasus, 2020)
The paper presents epistolary sources in the Persian language from the collection of firmans of the Persian shahs addressed to Kaytag Utsmiys. The Institute of History, Archeology and Ethnography of RAS holds microfilms of these firmans received from the National Library of France, where the Utsmi collection came into possession in the second half of the 19th century. Copies of Persian shahs’ firmans addressed to the Kaytag utsmiys are also available in Georgian libraries. The copies are published by Georgian scholars, with interpretations and translations into Georgian and Russian. A comparative analysis of the documents revealed that the Georgian collection is more complete than the Paris one; the collections contain copies compiled by different katibs; textual inconsistencies and discrepancies in dating of the firmans have been revealed. In the present paper we consider facsimile of the firmans issued by Nadir Shah to one of the most influential Dagestan rulers of the first half of the 18th century – Kaytag utsmiy Akhmad Khan, and provide their content with respective commentaries. Firmans are valuable sources of information: they serve as a solid base for studying a complex, contradictory period, which contains many white spots in the history of the wars of Nadir Shah in Dagestan. The documents are also of high scientific value, shedding light on the policies of Nadir Shah in his territories, on the historical events associated with the liberation struggle of the Dagestan peoples, the policy of the Dagestan rulers. The struggle of the Dagestan mountaineers with the Iranian Shah lasted several years. A decisive victory over Nadir Shah occurred when the combined forces of the Avars, Kaytags, Akushins, Kumukhs, Tabasaranians and other Dagestan peoples took part in the fight against him in 1741-1742. Firmans convey the atmosphere of historical events: threats against rebellious mountaineers can be traced more often, the tone of Nadir’s letters, promising endless shah’s mercy in return for humility, is replaced by a formidable, sometimes offensive one. The decline of power of Nadir Shah started in Dagestan, in the grueling wars with the mountaineers. The defeat of the previously invincible army of the Iranian shah closed the inglorious page of the military campaign in Dagestan.